Three-phase qZ-source inverter with fault tolerant capability - Fernao Pires, Vitor (2019)
The requirement of three-phase inverters with high reliability capability is considered important in several applications. Most of the adopted fault-tolerant solutions use classical three-phase voltage source inverters (VSI) with redundant controlled power devices or modified control strategies for acceptably degraded performance in the event of a failure yielding the loss of devices. This work proposes the use of a fault-tolerant converter based on the quasi-Z-source inverter (qZSI). This inverter presents important features such as boost capability and not requires dead time circuits. These features associated to the proposed topology results in a converter with high reliability and fault-tolerant capability. The proposed topology is designed to allow the reconfiguration of the converter after a power switch failure, using only two legs in the faulty mode. Additionally, this topology avoids extra inductors, capacitors and active power switches for the fault-tolerant condition. A current controller associated to a vectorial voltage modulator is used to control the proposed topology, which results in three-phase balanced AC currents with reduced total harmonic distortion even in faulty condition. The performance of this solution is confirmed through experimental results obtained from a laboratory prototype.